Adipose inflammation initiates recruitment of leukocytes to mouse femoral artery: role of adipo-vascular axis in chronic inflammation. - Sumihiko Hagita (PLoS ONE, 2011)
BACKGROUND: Although inflammation within adipose tissues is known to play a role in metabolic syndrome, the causative connection between inflamed adipose tissue and atherosclerosis is not fully understood. In the present study, we examined the direct effects of adipose tissue on macro-vascular inflammation using intravital microscopic analysis of the femoral artery after adipose tissue transplantation. METHODS AND RESULTS: We obtained subcutaneous (SQ) and visceral (VIS) adipose tissues from C57BL/6 mice fed normal chow (NC) or a high fat diet (HF), then transplanted the tissues into the perivascular area of the femoral artery of recipient C57/BL6 mice. Quantitative intravital microscopic analysis revealed an increase in adherent leukocytes after adipose tissue transplantation, with VIS found to induce significantly more leukocyte accumulation as compared to SQ. Moreover, adipose tissues from HF fed mice showed significantly more adhesion to the femoral artery. Simultaneous flow cytometry demonstrated upregulation of CD11b on peripheral granulocyte and monocytes after adipose tissue transplantation. We also observed dominant expressions of the inflammatory cytokine IL-6, and chemokines MCP-1 and MIP-1β in the stromal vascular fraction (SVF) of these adipose tissues as well as sera of recipient mice after transplantation. Finally, massive accumulations of pro-inflammatory and dendritic cells were detected in mice with VIS transplantation as compared to SQ, as well as in HF mice as compared to those fed NC. CONCLUSION: Our in vivo findings indicate that adipose tissue stimulates leukocyte accumulation in the femoral artery. The underlying mechanisms involve upregulation of CD11b in leukocytes, induction of cytokines and chemokines, and accumulation of pro-inflammatory cells in the SVF.